The influence of motivational factors on the performance of female employees at Majlis Bandaraya Alor Setar, Kedah. / Nurul Nadiah Abdul Rashid ... [et al.] - Abdul Rashid, Nurul Nadiah; Ismail, Rohana (2018)
To recruit, manage and retain the highly qualified and skilled workforce is a challenging task for the organizations. Hence, there is a need to develop human resources management policies and procedures that support the female employees at workplace (Irfan, Hussain &Yousaf, 2009). It is advisable to give the chance for female to share equally with male in the development of the community by reaching all the positions whatever are these. This is because, the female employees also have their own ability and skill in performing works towards development of organization and community.